Predictors of medication use during pregnancy: a cohort study (Epidemiology, Biostatistics, and Public Health, 2022)
BackgroundSociodemographic characteristics and health behaviours are associated with medication use in pregnancy, but it is unclear if they are independent predictors because women´s health status has hardly been accounted for. We aimed to identify predictors of use of medications and of iron/folic acid.MethodsThis cohort included pregnant women recruited in a prenatal clinic in Trieste, Italy, from 2007 to 2009. Dispensations were obtained from the regional outpatient dispensation database through record linkage. We calculated the Odds Ratio (OR), with 95% confidence interval (95%CI), of ≥ 1 dispensation of (a) any medication and (b) iron/folic acid, using unconditional logistic regression. The final model adjusted for age, partner education, housing size, comorbidities. FindingsOf 767 women, 70.5% had ≥ 1 dispensation of any medication and 46.1% of iron/folic acid. Use of any medication was predicted by immigrant status of the woman (OR 1.21; 95%CI 0.57–2.53) or of her partner (1.51; 0.67–3.40), ≤ high school degree of the woman (1.11; 0.61–2.03) or of her partner (1.21; 0.75–1.95), unemployment (1.47; 0.72–2.98), smoking (1.25; 0.65–2.40), alcohol consumption (≥5 drinks/week: 2.78; 1.78–4.34), and obesity (1.33; 0.59–2.99). Use of iron and/or folic acid was predicted by ≤ high school degree (0.65; 0.40–1.08), smoking (0.80: 0.47–1.37), and obesity (0.62; 0.31–1.25).DiscussionIn this cohort, characteristics including education, immigrant and employment status, smoking, alcohol consumption, and obesity independently predicted medication use. Interventions to promote safe use of medications should carefully consider women´s characteristics.